2023
DOI: 10.1038/s41598-023-31250-2
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine D2-like receptors availability in obesity and its modulation by bariatric surgery: a systematic review and meta-analysis

Abstract: There is significant evidence linking a ‘reward deficiency syndrome’ (RDS), comprising decreased availability of striatal dopamine D2-like receptors (DD2lR) and addiction-like behaviors underlying substance use disorders and obesity. Regarding obesity, a systematic review of the literature with a meta-analysis of such data is lacking. Following a systematic review of the literature, we performed random-effects meta-analyses to determine group differences in case–control studies comparing DD2lR between individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
6
0
1
Order By: Relevance
“…Furthermore, mesoaccumbens hypo‐connectivity in addiction was found to be inversely associated with years of cocaine use [39] and the severity of internet addiction [35], suggesting that altered mesoaccumbens connectivity may be evident in more severe cases of obesity (on average, our sample of patients were in the mild‐to‐moderate range of the obesity spectrum: average BMI = 36 kg/m 2 , comprising obesity class I and II) or in patients with obesity showing severe addiction‐like symptoms. Supporting this interpretation, a recent meta‐analysis of dopamine availability studies in obesity showed that only severe cases of obesity (class III or higher) display a significant reduction in dopamine availability in the striatum, whereas mild to moderate obesity (class I and II) do not [41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mesoaccumbens hypo‐connectivity in addiction was found to be inversely associated with years of cocaine use [39] and the severity of internet addiction [35], suggesting that altered mesoaccumbens connectivity may be evident in more severe cases of obesity (on average, our sample of patients were in the mild‐to‐moderate range of the obesity spectrum: average BMI = 36 kg/m 2 , comprising obesity class I and II) or in patients with obesity showing severe addiction‐like symptoms. Supporting this interpretation, a recent meta‐analysis of dopamine availability studies in obesity showed that only severe cases of obesity (class III or higher) display a significant reduction in dopamine availability in the striatum, whereas mild to moderate obesity (class I and II) do not [41].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the surgical intervention directly modulated the dopaminergic reward system. It is known that D2 availability can decrease with overstimulation from overeating [105][106][107] and D2 striatal receptor availability is significantly decreased in cases of severe obesity [28]. These results suggest that surgery bypassed D2 super sensitivity and decreased the wanting mechanism in these obese patients.…”
Section: Discussionmentioning
confidence: 82%
“…The A1 risk allele is associated with various substance and nonsubstance addictions [70,94,95]. Carriers of this risk allele show a decreased availability of dopamine D2 receptors [96,97], which can result in D2 receptor super-sensitivity [98], increasing severity of alcoholism [99,100], obesity [28], and addiction relapse [98].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values were set based on a meta-analysis performed to investigate group differences in case–control studies comparing the same central dopamine receptors between individuals with obesity and non-obese controls. 36 In the case of significant differences, the overall Cohen’s d was −1.16 0.71.…”
Section: Methods and Analysismentioning
confidence: 98%